The Female Reproductive Tract: Congenital Concerns - Dietrich, J. E. (Hormone and Metabolic Research, 2015)
The incidence and prevalence of conditions of the reproductive tract varies. This is related to both the complexity and spectrum of underlying and associated conditions. In some cases, only retrospective or case data are available, and likely under-reporting occurs, contributing to a lower than expected prevalence. Given the complex nature in which the reproductive tract develops in the fetus, it is important to understand the embryology, especially in situations of congenital anatomic differences. It is interesting to note not only patterns of conditions, but patterns of concurrent conditions or anomalies such as those occurring with isolated Müllerian anomalies, in conjunction with disorders of sexual differentiation or with cloacal malformations. This review will address typical presentation of these conditions, highlights of management and point to areas of research need, including clinical outcomes and genetic implications.
Keywords: sexual differentiation; Müllerian anomalies; androgen